RXP-E: A CX43-BINDING PEPTIDE THAT PREVENTS ACTION POTENTIAL PROPAGATION BLOCK - Lewandowski, Rebecca (2008)
Gap junctions (GJs) provide a low-resistance pathway for cardiac electrical propagation. The role of GJ regulation in arrhythmia is unclear, partly due to limited availability of pharmacological tools. Recently, we showed that a peptide called “RXP-E” binds to the carboxyl terminal of connexin43 (Cx43) and prevents chemically-induced uncoupling in Cx43-expressing N2a cells. Here, pull-down experiments show RXP-E binding to adult cardiac Cx43. Patch-clamp studies revealed that RXP-E prevented heptanol-induced and acidification-induced uncoupling in pairs of neonatal rat ventricular myocytes (NRVM’s). Separately, RXP-E was concatenated to a cytoplasmic transduction peptide for cytoplasmic translocation (CTP-RXP-E). The effect of RXP-E on action potential (AP) propagation was assessed by high resolution optical mapping in monolayers of NRVM’s, containing ~20% of randomly distributed myofibroblasts. In contrast to control experiments, when heptanol (2 mmol/L) was added to the superfusate of monolayers loaded with CTP-RXP-E, AP propagation was maintained, albeit at a slower velocity. Similarly, intracellular acidification (pHi=6.2) caused a loss of AP propagation in control monolayers; however, propagation was maintained in CTP-RXP-E treated cells, though at a slower rate. Patch clamp experiments revealed that RXP-E did not prevent heptanol-induced block of sodium currents, nor did it alter voltage dependence or amplitude of Kir2.1/Kir2.3 currents. RXP-E is the first synthetic molecule known to: (1) bind cardiac Cx43; (2) prevent heptanol and acidification-induced uncoupling of cardiac GJ’s and 3) preserve AP propagation among cardiac myocytes. RXP-E can be used to characterize the role of GJs in the function of multicellular systems, including the heart.